Market misreaction? Evidence from cross-border acquisitions - CNV Krishnan; Jialun Wu (Journal of Risk and Financial Management, 2022)
Our goal in this paper is to answer this research question: Do investors understand the longer-term value-implications of cross border mergers and acquisitions, as at the time of their announcements? We examine acquirers' operating efficiencies around and after cross-border acquisitions and relate this to the announcement-period stock-market reaction. Using a dataset of cross-border mergers and acquisitions (M&A) entailing U.S. acquirers over the period 1990-2013, and using a bootstrapped-DEA (Data Envelopment Analysis) model because any one indicator may not reflect the whole performance of the merger, we find that the operating efficiency of the acquirers decreases around the acquisition, and up to three years after. However, we document evidence of stock market mis-reaction at announcement: the announcement-period acquirer abnormal stock-price return is not significantly associated with acquirer's operating efficiency post-acquisition. Therefore, investors should be careful interpreting the announcement-period stock-price reaction in cross-border mergers and acquisitions as indicative of merger efficiency gains.
Keywords: 330; cross-border M&A; merger efficiency; operating efficiency; abnormal returns